IL (Interleukin)-33 Suppresses Abdominal Aortic Aneurysm by Enhancing Regulatory T-Cell Expansion and Activity. Issue 3 (March 2019) - Li, Jingyong; Xia, Ni; Wen, Shuang; Li, Dan; Lu, Yuzhi; Gu, Muyang; Tang, Tingting; Jiao, Jiao; Lv, Bingjie; Nie, Shaofang; Liao, Mengyang; Liao, Yuhua; et al.
Abstract : Objective—: Inflammation occurs during the progression of abdominal aortic aneurysm (AAA). IL (interleukin)-33 is a pleiotropic cytokine with multiple immunomodulatory effects, yet its role in AAA remains unknown. Approach and Results—: Immunoblot, immunohistochemistry, and immunofluorescent staining revealed increased IL-33 expression in adventitia fibroblasts from mouse AAA lesions. Daily intraperitoneal administration of recombinant IL-33 or transgenic IL-33 expression ameliorated periaorta CaPO4 injury- and aortic elastase exposure–induced AAA in mice, as demonstrated by blunted aortic expansion, reduced aortic wall elastica fragmentation, enhanced AAA lesion collagen deposition, attenuated T-cell and macrophage infiltration, reduced inflammatory cytokine production, skewed M2 macrophage polarization, and reduced lesion MMP (matrix metalloproteinase) expression and cell apoptosis. Flow cytometry analysis, immunostaining, and immunoblot analysis showed that exogenous IL-33 increased CD4 + Foxp3 + regulatory T cells in spleens, blood, and aortas in periaorta CaPO4 -treated mice. Yet, ST2 deficiency muted these IL-33 activities. Regulatory T cells from IL-33–treated mice also showed significantly stronger activities in suppressing smooth muscle cell inflammatory cytokine and chemokine expression, macrophage MMP expression, and in increasing M2 macrophage polarization than those from vehicle-treated mice. In contrast, IL-33 failed to prevent AAA and lost its beneficial activities in CaPO4 -treated mice after selective depletion of regulatory T cells. Conclusions—: Together, this study established a role of IL-33 in protecting mice from AAA formation by enhancing ST2-dependent aortic and systemic regulatory T-cell expansion and their immunosuppressive activities. Abstract : Supplemental Digital Content is available in the text.